2015
DOI: 10.3390/nu7075222
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Prevents L-NAME-Induced Hypertension via Restoration of eNOS and p47phox Expression in Rats

Abstract: The effect of ellagic acid on oxidative stress and hypertension induced by Nω-Nitro-l-arginine methyl ester hydrochloride (L-NAME) was investigated. Male Sprague-Dawley rats were administrated with L-NAME (40 mg/kg/day) for five weeks. L-NAME induced high systolic blood pressure (SBP) and increased heart rate (HR), hindlimb vascular resistance (HVR) and oxidative stress. Concurrent treatment with ellagic acid (7.5 or 15 mg/kg) prevented these alterations. Co-treatment with ellagic acid was associated with up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 57 publications
6
52
1
2
Order By: Relevance
“…One such polyphenol is ellagic acid (EA) which is found in berries, grapes, pomegranates, and nuts. It has received increasing attention in the scientific community due its potential as an anti-inflammatory [26,27] and antioxidant [28][29][30] compound. A recent study has demonstrated that EA lowered blood pressure in hypertensive rats via an antioxidant effect of EA which includes increased nitric oxide synthase (NOS) expression and decreased ROS levels in the plasma [28].…”
Section: Introductionmentioning
confidence: 99%
“…One such polyphenol is ellagic acid (EA) which is found in berries, grapes, pomegranates, and nuts. It has received increasing attention in the scientific community due its potential as an anti-inflammatory [26,27] and antioxidant [28][29][30] compound. A recent study has demonstrated that EA lowered blood pressure in hypertensive rats via an antioxidant effect of EA which includes increased nitric oxide synthase (NOS) expression and decreased ROS levels in the plasma [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide is a potent vasodilator, it maintains vascular tone, inhibit platelet aggregation, monocyte adhesion, smooth muscle proliferation/migration and regulates BP [10,19]. Therefore loss or decrease of NO production due to inhibition of nitric oxide synthase by L-NAME plays an important role in pathogenesis of HTN.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NO exerts direct inhibitory effects on renal tubular function through the inhibition of both the Na + /K + -ATPase and the Na + /H + exchanger therefore, reducing sodium reabsorption and increasing natriuresis/diuresis [23]. Excessive production of reactive oxygen species is proposed to be a major factor in mediating the pathogenesis of HTN [19]. In the L-NAME model, a large quantity of superoxide production suppresses nitric oxide bioavailability [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…≪靈樞ㆍ邪氣臟腑病形≫에서는 "滎腧治外經, 合治內府"라고 하여 五輸穴의 效果가 있음을 밝히고 있다 35) . , 최근 항고혈압 효과를 관찰하기 위한 여러 연구에 활용되고 있다 46,47) . …”
Section: 항산화능(Antioxidative Effectiveness)에 미치는 효과unclassified